1997
DOI: 10.1074/jbc.272.29.18397
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of the cGMP-binding cGMP Phosphodiesterase by Proteins That Are Immunologically Related to γ Subunit of the Photoreceptor cGMP Phosphodiesterase

Abstract: The cGMP phosphodiesterase from retinal rods (PDE-6) is an ␣␤␥ 2 heterotetramer. The ␣ and ␤ subunits contain catalytic sites for cGMP hydrolysis, whereas the ␥ subunits serve as a protein inhibitor of the enzyme. Visual excitation of photoreceptors enables the activated GTP-bound form of the G-protein transducin to remove the inhibitory action of the ␥ subunit, thereby triggering PDE-6 activation. The type 5 phosphodiesterase (PDE-5) isoform shares a number of similar characteristics with PDE-6, including bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

1998
1998
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 33 publications
1
26
1
Order By: Relevance
“…Photoreceptor PDEs (PDE6), which are homologous to cGB-PDE, are known as membrane-associated proteins and are inhibited by ␥ subunits of PDE6 on retinal membrane (5). The PDE6 ␥ subunit is also noted to prevent the activation of cGB-PDE by cAMP-dependent protein kinase (42). It was reported that a form of the PDE4 family, named RNPDE4A5, interacted with SH3 domain of Src tyrosyl protein kinase, and that its activity is regulated by such proteins (28).…”
Section: Resultsmentioning
confidence: 99%
“…Photoreceptor PDEs (PDE6), which are homologous to cGB-PDE, are known as membrane-associated proteins and are inhibited by ␥ subunits of PDE6 on retinal membrane (5). The PDE6 ␥ subunit is also noted to prevent the activation of cGB-PDE by cAMP-dependent protein kinase (42). It was reported that a form of the PDE4 family, named RNPDE4A5, interacted with SH3 domain of Src tyrosyl protein kinase, and that its activity is regulated by such proteins (28).…”
Section: Resultsmentioning
confidence: 99%
“…20,35,36 The g subunit of PDE6 also acts as a substrate for phosphorylation at several distinct sites within the central region of this 10 kDa protein. Phosphorylation of g at Thr (22) or Thr (35) has little effect on the PDE6 holoenzyme itself, but greatly diminishes the ability of activated transducin to bind the g subunit and relieve inhibition of catalysis. 37 Phosphorylation of g at Thr(62) in nonretinal tissue has been reported to regulate mitogenic signaling via interactions with proteins other than PDE6 catalytic subunits (whose expression is confined to the retina and pineal gland).…”
Section: S30mentioning
confidence: 99%
“…3 For PDE5, enzyme activation most likely proceeds via phosphorylation of the catalytic subunits and allosteric changes in cGMP binding to the GAF domains. 20,21 (While PDE5 has been reported to copurify with the PDE6 g subunit, 22 the physiological significance is uncertain because the g subunit lacks binding or inhibitory activity toward PDE5 in vitro. 23 )…”
Section: Similarities and Differences Between Pde5 And Pde6mentioning
confidence: 99%
“…Burns et al (57) have reported that a partially purified PDE5 from guinea pig lung is activated when phosphorylated by PKA. PDE5 may also be regulated by other low molecular weight factors, and these could alter the effects of phosphorylation (58). As is the case for PDE4, PDE5 may also be subject to long term regulation through changes in enzyme concentration in some cell types (59 -61).…”
Section: Properties Of Pde5mentioning
confidence: 99%